The Relationship Between Sanitation Facilities and Dengue Fever Incidents on Jl. Aman, Tanjung Balai City, Simardan Island - Nanda, Meutia; Sibarani, Adinda Azima Riskiya; Rizki, Aprida Aulia; Natasya, Diva Aulia Aulia; Syahputri, Nuri Nabila (Fakultas Ilmu Kesehatan, 2024)
The incidence of dengue fever is closely related to sanitation facilities that invite Aedes aegypti mosquitoes to breed and become a disease problem that always occurs every year, including in Tanjung Balai City, around 70 cases of people contracting dengue fever and this is an endemic area for dengue fever in 2023. This research aims to determine the relationship between sanitation facilities and the incidence of dengue fever on the Safe Road in Tanjung Balai City, Simardan Island. This research uses a quantitative approach with a cross-sectional method, the population in this study is the entire community on safe roads totaling 170 people and the total sample in this study is 60 people. Based on the results of the analysis, it was found that there was a relationship between garbage disposal (p value = 0.032) and water storage (p value = 0.015) with the incidence of DHF in Jalan Aman Kota Tanjung Balai Simardan Island. It is hoped that this research can provide awareness to the government and health workers to carry out outreach and supervision to the public regarding the importance of maintaining the sanitary conditions of the home environment in good condition.